Arahan Spasial Teknologi Drainase Untuk Mereduksi Genangan Di Sub Daerah Aliran Sungai Watu Bagian Hilir - Kusumadewi, Diah Ayu; Bisri, M. (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
The high population growth have led to higher demand for housing and supporting infrastructure, but the area is relatively fixed. This leads causing high conversion of open space to be built. So if it rains, there is always a pool. In downstrean Sub Water Catchment Area of Watu is one of the quite interested location for developers to build housing. Recorded at the studied location, increased number of sites pool with long pool and varying height of pools. On the other hand there has been no approach to handling spatial puddle of water, so as to create spatial land by providing an appropriate space for water to enter the maximum into the ground through infiltration process. The purpose of this study is to provide the spatial direction of drainage techniques to reduce puddles on the Lower Sub-basin Watu. The method used were descriptive method, through the analysis of land use, water absorption analysis, analysis of the rate of surface runoff and drainage system analysis. Analyses were performed on data with the data existing in the year 2010 based on the end year plan from Kota Malang Spatial Plan Year 2010-2030. Based on the analysis, in 2010, woke up the living space is 207.36 ha (31.82%) and 444.36 ha of open space (68.18%). In the year 2030 an increase in space woke up onto 417.97 ha (64.13%) followed by reduction of open space to be 233.75 ha (35.87%). A decrease in water absorption of the Year 2010 m3/year 240,888.40 to 117,444.40 m3/year in the year 2030. And an increase in flow rate on the surface of m3/second 118.622 136.874 m3/second Year 2010 to the Year 2030. From the analysis of the drainage system obtained 33% of the existing conditions are not available drainage, drainage channels covered 17% of the building, 6% of the drainage channels double as irrigation canals, drainage channels 10% too small, 14% with no inlet or drainage channels lip channels higher than face the street, 11% poorly maintained drainage channel or channels overgrown with grass, and 8% tract in good condition.By looking at the result of data analysis and assessment of existing theory, then the directives of spatial technology to reduce the pool of drainage in Sub Water Catchment Area of Watu is the eco-drainage technology or drainage eco-friendly environment, which synergize with the spatial practices of water conservation. Spatial direction of eco-drainage in the Lower Sub-basin Watu are (1). The separation between the drainage channel that drains domestic wastewater with rain water drainage, (2). Preparation of individual wells on the main road corridors, particularly in the residential building medium, large residential, commercial and service facilities, industry and warehousing facilities, education and health facilities, (3). Making collective wells at high density buildings, especially residential buildings are very small and small / simple, and (4). Creating a catchment pond for formal housing in the topography of the basin.